Exponential equation
Initial explanation
If we apply the exponential equation to a finantial situation, were you invest some value of money and you receive (or loose) a percentage of it, then we will have that the equation will have the form:
![A=a(1\pm r)^t](https://img.qammunity.org/2023/formulas/mathematics/college/6431vn4qerbxiudybb5vvtqt710a6e9eyh.png)
Its parts are:
- a: initial value
- r: growth or decreasing rate
- t: time
- A: total amount of money
Finding a simplified equation for this case
Then, in this case
- a = $120
- r = 7.25% = 7.25/100 = 0.0725
Since it is a growth rate then it is an addition +
- t = 2 years
- A: total amount of money
Replacing in the equation, we have that:
![\begin{gathered} A=a(1\pm r)^t \\ \downarrow \\ A=120(1+0.0725)^2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/zcorl55j0nb2ec2m7a9wz4gjvqob0vj6ry.png)
Total amount of money after two years
If we solve the previous simplified equation, we have that:
![\begin{gathered} A=120(1+0.0725)^2 \\ \downarrow \\ A=120(1.0725)^2 \\ A=120\cdot1.50=138.03075 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/k85hw9vkvh3v99tzlo996dlm54cvabdamo.png)
After two years, the total amount of money (including the growth rate) is
$138.03075.